P-046. Evaluation of buccal mucous sensitivity to various toothpastes. Clinical study in patientes submitted to radiotherapy - Biazolla, E. R. [UNESP]; Mota, C. S. [UNESP]; Souza, S. P. [UNESP]; Conrado-Neto, S. [UNESP] (My University, 2001)
Aim: Radiotherapy causes some discomfort in the mouths of patients, caused by the peeling of the buccal epithelium, followed by erythema and pain. At this stage, it is noted that some patients neglect oral hygiene, alleging it to be due to sensitivity of the mucous membrane. Thus, some toothpastes were studied in an attempt to find one that was not irritating and would cause less sensitivity to these patients. Methods: An analysis was made of 21 patients registered with the Oral Cancer Center of the Paulista State University -Unesp, Aracatuba Campus, Brazil, who received radiotherapy in the cervical-facial field. The patients were divided into two groups, group I was composed of patients that were in the course of radiotherapy and up to 3 months from the end of it. Group II was composed of patients that had concluded radiotherapy over 3 months ago. In this study six toothpastes, denominated A, B, C, D, E, F were analyzed. The parameter used for evaluation was information from the patient, with regard to the degree of sensitivity as strong, moderate, light or absent. The statistical analysis of the results was done by means of the nonparametric Kruskal-Wallis test Results: The comparison between the information from Groups I and II indicated that paste B showed the greatest irritability to the buccal mucous (Q = 5.4697) in the patients exposed to radiotherapy. The difference between the chemical compositions of the tooth pastes A, C, D, E, F and B was chlorophyll. Conclusion: Toothpastes that have chlorophyll in them produce greater discomfort to patients.